2008
DOI: 10.1090/s0002-9947-08-04413-9
|View full text |Cite
|
Sign up to set email alerts
|

Exponential separation and principal Floquet bundles for linear parabolic equations on general bounded domains: Nondivergence case

Abstract: Abstract. We consider the Dirichlet problem for linear nonautonomous second order parabolic equations of nondivergence type on general bounded domains with bounded measurable coefficients. Under such minimal regularity assumptions, we establish the existence of a principal Floquet bundle exponentially separated from a complementary invariant bundle. As a special case of our main theorem, assuming the coefficients are time-periodic, we obtain a new result on the existence of a principal eigenvalue of an associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Besides, when no advection appears, Du and Peng in [27,28] considered the case that V (x, t) = μv(x, t), where v(x, t) ≥ 0, ≡ 0 may vanish somewhere, and studied the asymptotic behavior of λ 1 as μ → ∞, which turns out to be essentially different from that of the autonomous elliptic counterpart. For some other recent work on the periodic-parabolic eigenvalue problems and related applications, one may further refer to [14,18,19,37,40,48,50]; on the other hand, the study on the principal eigenvalue for cooperative systems can be found in [2][3][4]12,13,15] and the references therein.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, when no advection appears, Du and Peng in [27,28] considered the case that V (x, t) = μv(x, t), where v(x, t) ≥ 0, ≡ 0 may vanish somewhere, and studied the asymptotic behavior of λ 1 as μ → ∞, which turns out to be essentially different from that of the autonomous elliptic counterpart. For some other recent work on the periodic-parabolic eigenvalue problems and related applications, one may further refer to [14,18,19,37,40,48,50]; on the other hand, the study on the principal eigenvalue for cooperative systems can be found in [2][3][4]12,13,15] and the references therein.…”
Section: Introductionmentioning
confidence: 99%
“…This is hardly an optimal result, although restricting the class of admissible solutions is probably necessary for the uniqueness. Similar uniqueness problems for bounded domains have been addressed in several papers, see for example [11,13,14,16,23,24,29]. A different result for nonautonomous equations on time-dependent domains can be found in [28].…”
Section: Statement Of the Main Resultsmentioning
confidence: 63%
“…An approach based on maximum principles for small domains as in [6] would have the advantage of requiring weaker regularity assumptions on the nonlinearity, but this technique typically only guarantees asymptotic positivity of (v e ′ n , u e ′ 2 ) and therefore, to perform a perturbation argument, one needs that the coefficients of the linearization are uniformly bounded independently of (v e ′ n , u e ′ 2 ) for all times, which, as explained above, does not happen in general. For scalar equations, eventual positivity using maximum principles for small domains was obtained in [8,Proposition 6.11], but an extension of this result to the case of linear systems remains, up to our knowledge, an open question.…”
Section: Dirichlet Parabolic Systemsmentioning
confidence: 99%